Delta H reaction for the following reaction: C(s)+H2O(g)=>CO(g)+H2(g) Use the following reactions a?

NetherCraft 0

Calculate Delta H reaction for the following reaction:?

Calculate Delta H reaction for the following reaction: C(s)+H2O(g)=>CO(g)+H2(g) Use the following reactions a?

Please Help! I DO need the ANSWER BUT MORE IMPORTANT I need the STEPS to the Answer!

Calculate Delta H reaction for the following reaction:

C(s)+H2O(g)=>CO(g)+H2(g)

Use the following reactions and given Delta H:

C(s)+O2(g)=>CO2(g), Delta H= -393.5 kJ

2CO(g)+O2(g)=>2CO2(g) , Delta H= -566.0 kJ

2H2(g)+O2(g)=>2H2O(g) , Delta H= -483.6 kJ

Answer in 4 sig figs, for kJ

Also Check This  How to make myself colorblind permanently?

3 Answers

  • rearrange the second equation to obtain CO on the other side of the equation(Delta H is now reversed for that equation, 556.0kJ)

    do the same for the third equation to obtain H2 on the other side; swith Delta H

    Combine all three equations, and cancel like terms:

    C(s)+O2(g)+2CO2(g)+2H2O(g)=CO2(g)+2CO(g)+O2(g)+2H2(g)+O2(g)

    After cancelling you should get:

    2C(s)+2H2O(g)=2CO(g)+2H2(g)

    Add all Delta H’s(-393.5+566+483.6)=656.1kJ

    Because this is for 2 moles of everything, you have to half the answer:

    328.1kJ

  • Reverse the second and third equations. After doing so change the signs of the Delta H’s of said equations. After that half the same equations.

    C(s)+O2(g)==>CO2(g) Delta H = -393.5kJ

    2CO(g)+O2(g)=>2CO2(g) Delta H= -566.0 kJ

    2H2(g)+O2(g)=>2H2O(g) Delta H= -483.6 kJ

    then becomes:

    C(s)+O2(g)==>CO2(g) Delta H = -393.5kJ

    CO2(g)==>CO(g)+.5O2(g) Delta H = 283.0 kJ

    H2O(g)==>H2(g)+.5O2(g) Delta H = 241.8 kJ

    After cancelling like terms you will end up with the target equation, C(s)+H2O(g)==>CO(g)+H2(g).

    Add the Delta Hs and you’ll get 131.3 kJ

  • Marquise is absolutely right!!

    The answer is indeed 131.3 kJ


Leave a Reply

Your email address will not be published. Required fields are marked *